First report of Erwinia psidii associated with papaya dieback disease in Malaysia - Chai, Wan Ting; Jualang Azlan Gansau; Markus Atong; Jugah Kadir; Evenni Poili; Chong, Khim Phin (Malaysian Society for Microbiology, 2017)
Aims: The outbreak of papaya dieback disease in Malaysia has been reported since 2003. Several reports previously confirmed Erwinia papayae and E. mallotivora to be the causal pathogen of the disease. The present study aimed to identify the causal pathogen of papaya dieback disease in Sabah.